Major facility superfamily sugar transporter protein SsMFSST1 regulates Sporisorium scitamineum mating, pathogenicity, and sugar transport/absorption - Yi Zhang; Yongding He; Meixin Yan; Shilong Zhang; Sisi Zhou; Wankuan Shen (Microbiology Spectrum)
ABSTRACT Sugarcane smut caused by Sporisorium scitamineum is a global sugarcane disease, and studying its molecular pathogenesis is crucial for discovering new prevention and control targets. This study was based on the transcriptome sequencing data of two isolates with different pathogenicities (Ss16 and Ss47) of the S. scitamineum and screened out a gene encoding the Major Facility Superfamily (MFS) sugar transporter protein and named it SsMFSST1. Knockout mutants (∆SsMFSST1+ and ∆SsMFSST1−) and complementary mutants (COMMFSST1+ and COMMFSST1−) were obtained through polyethylene glycol (PEG)-mediated protoplast transformation technology. On this basis, the function of gene SsMFSST1 was analyzed. The research results showed that the sexual mating ability of the knockout mutants significantly decreased compared with the wild type, while the sexual mating ability of the complementary mutants was almost restored to the level of the wild type. After the addition of exogenous small molecular signaling substance cyclic adenosine monophosphate (cAMP) or tryptophol required for the sexual mating of S. scitamineum, the sexual mating ability of the knockout mutants was almost restored to the level of the wild type. It was observed that the expression levels of the key genes Uac1 for cAMP synthesis and Aro8 for tryptophol synthesis were significantly lower in the knockout mutants compared with the wild type. However, the expression levels of these genes in the complementary mutants were restored to the wild-type levels. The pathogenicity testing also found a significant decrease in the pathogenicity of combinations containing mutants. On YePSA medium, the gene SsMFSST1 does not affect the growth, spore morphology, colony morphology, and oxidative stress ability of the haploid spores of S. scitamineum. Therefore, we speculate that the SsMFSST1 gene may regulate the expression of key genes related to the synthesis pathway of the small molecule signaling substance cAMP or tryptophol, affecting the synthesis of the signaling substance cAMP or tryptophol, thereby affecting the sexual mating and pathogenicity of S.scitamineum. In addition, this gene also regulates the transport/absorption of fructose and lactose in S. scitamineum. In summary, this study identified a novel pathogenic gene in the S. scitamineum—the MFS sugar transporter gene, providing a molecular basis for understanding the pathogenic mechanism of the S. scitamineum. On the other hand, it also enriches the biological functions of this gene in fungi.IMPORTANCESugarcane is an important economic crop, but the sugarcane smut disease caused by S. scitamineum severely damages the yield and quality of sugarcane, causing huge economic losses on the sugarcane industry. Therefore, it is very necessary to study the pathogenic mechanism of S. scitamineum, especially at the molecular level. This manuscript identified a new pathogenic gene and discovered a new pathogenic mechanism of this gene in S. scitamineum, enriched the molecular pathogenesis of S. scitamineum, and provided a new target for the prevention and control of sugarcane smut disease.